Effect of the thickness to length ratio on the frequency ratio of nanobeams and nanoplates - Bahrami, Arian; Shiri, Hamidreza; Khosravi, Nima (Polish Society of Theoretical and Allied Mechanics Al. Armii Ludowej 16 p. 650 Warszawa 00637, 2020)
This communication presents the effect of thickness on the frequency ratio of nanobeams and nanoplates using Eringen’s nonlocal theory. Although there exist numerous works regarding the effects of thickness and small scale on the frequency ratio of nanobeams and nanoplates, none has captured and reported the true effects. The main intention of this communication is to correct the misunderstanding regarding this issue. It was found that the frequency ratio is indeed dependent on the thickness to length ratio and its variation with respect to thickness to length ratio is highly dependent on the mode number, combination of boundary conditions, plate aspect ratio, and the nonlocal parameter. © 2020 Polish Society of Theoretical and Allied Mechanics. All rights reserved.
Keywords: Frequency ratio; Nanobeam; Nanoplate; Nonlocal elasticity; Thickness